Persepsi Konsumen terhadap Daging Kerbau dan Daging Sapi di Kecamatan Candipuro Kabupaten Lumajang - Permata, A. M.; Komariah, Komariah; Cyrilla, L. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2018)
Consumer of buffalo meat in Indonesia are low because of it’s negative image. Consumer has perception that buffalo meat has tough and hard texture, dark color, and strong smell which makes it less favored. This research aims to identify the consumer’s characteristic and perceptions on buffalo meat and beef also to analyze the relationship of perceptions and consumer’s characteristic. This research used 50 respondents with purposive sampling technique. The research method used are descriptive analysis to describe characteristic and perception of consumer and correlational test Rank Spearman to know relation between consumer characteristic and perception with buffalo meat. The result showed that consumer’s perception in Candipuro Subdistrict prefered beef (64%) than buffalo meat (36%). The average score of perception shows that consumers have good perception on buffalo meat with a score of 2.28. Aspects of product quality is the aspect with the lowest score of 2.00 and the aspect with the highest score is the religion aspect with a score of 3.00. The result correlational test Rank Spearman showed that occupation and in direction with consumer perseption rate of buffalo meat.